Representing European Civil Society: A Decentred And Political Approach - Kutay, Acar (Routledge Journals, Taylor & Francis Ltd, 2022)
From the Maastricht treaty to the economic crisis in 2008, the practitioners were inclined to associate European Civil Society (ECS) with the EU supported- large NGOs located in Brussels. The EU institutions, particularly the European Commission, aimed to involve the citizens' interests, demands, and concerns through the organised actors of civil society when the EU was deemed to suffer from a democratic deficit and political legitimacy. This practice of mobilizing the organised actor of civil society within the scope of participatory governance would allay these concerns. Nonetheless, since the economic crisis in 2008, the EU institutions' focus on Brussels-based NGOs has become less prominent. On the one hand, the launching of the European Citizens Initiative opened new venues for the EU to contact citizens directly. On the other hand, in addition to the economic crisis in 2008, other pressing issues, including the rise of the populist right, Brexit, and migration, had a tectonic effect on ECS. Such effects are yet to be analyzed, and this article offers a conceptual/interpretive analysis of this change. This new perspective decentres ECS and reconsiders how citizens' interests can be linked to the European governance and what it means to represent the EU's social constituency.
Keywords: European public sphere; interpretive theory; representation; civil society; social movements; decentred approach